2022
DOI: 10.3389/fonc.2022.891724
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Radiofrequency Ablation With Resiquimod to Treat Hepatocellular Carcinoma Via Inflammation of Tumor Immune Microenvironment and Suppression of Angiogenesis

Abstract: BackgroundRadiofrequency ablation (RFA) destroys tumors through hyperthermic injury, which induces the release of immunogenic intracellular substrates and damages associated molecular patterns (DAMPs) to evoke a systemic immune response, but its therapeutic effect is limited. This study aimed to combine RFA with an immunomodulator, resiquimod (R848), to enhance the RFA-induced antitumor immunity.MethodsWe performed RFA on subcutaneous tumors in immunocompetent mice and intraperitoneally injected R848 to observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…There has been longstanding interest in the capacity of ablation to activate tumor-directed immune responses. Measurable and occasionally abscopal anti-tumor immune responses have been observed with cryoablation, radiofrequency ablation and radiation, largely when used in combination with immunomodulatory agents like CpG or pro-inflammatory cytokines (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). We recently reported that histotripsy, a non-thermal mode of mechanical FUS ablation (32-36), stimulates potent local and abscopal CD8+ T cell infiltration and tumor inhibition as monotherapy; using murine models of melanoma and hepatocellular carcinoma, we observed that this effect can enhance checkpoint inhibition immunotherapy (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been longstanding interest in the capacity of ablation to activate tumor-directed immune responses. Measurable and occasionally abscopal anti-tumor immune responses have been observed with cryoablation, radiofrequency ablation and radiation, largely when used in combination with immunomodulatory agents like CpG or pro-inflammatory cytokines (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). We recently reported that histotripsy, a non-thermal mode of mechanical FUS ablation (32-36), stimulates potent local and abscopal CD8+ T cell infiltration and tumor inhibition as monotherapy; using murine models of melanoma and hepatocellular carcinoma, we observed that this effect can enhance checkpoint inhibition immunotherapy (37).…”
Section: Discussionmentioning
confidence: 99%
“…There is great interest in developing ablative therapies to trigger systemic anti-tumor immune responses that could augment the efficacy of cancer immunotherapy (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). By initiating immunogenic cell death pathways (e.g., necroptosis, pyroptosis) that release tumor-specific antigens within the context of pro-inflammatory danger signals, ablation could initiate the cancer immunity cycle of antigen presentation and adaptive immune stimulation (14).…”
Section: Introductionmentioning
confidence: 99%
“…The method for preparing single-cell suspensions was described previously . Briefly, mice were sacrificed 14 days after different treatments, and the tumor was cut into pieces, digested, and resuspended.…”
Section: Methodsmentioning
confidence: 99%
“… 71 In addition, RFA, combined with the immunomodulator Resiquimod (R848), can stimulate a stronger anti-tumor immune response, inhibit angiogenesis, promote cell apoptosis, and effectively inhibit the progression of HCC in mice in an NK cell-dependent manner. 133 Adoptive cellular therapy (ACT) has demonstrated great potential in immunotherapy tumors. ACT refers to extracting T cells from patients, culture, and modification in vitro , followed by reinfusion into the patient to destroy tumor cells.…”
Section: Strategies To Prevent and Treat Hcc Recurrence After Tamentioning
confidence: 99%